A taxonomic review of Longchuanacris Zheng et Fu (Orthoptera: Acrididae: Catantopinae), with descriptions of two new species from Yunnan, China - Mao, Ben-Yong; Ren, Guo-Dong; Ou, Xiao-Hong (Zootaxa, 2007)
The taxonomy of five species of the genus Longchuanacris Zheng et Fu, 1989 is revised. L. bilobatus, sp. nov. and L. curvifurculus, sp. nov. are described as new species. Caryanda bidentata Zheng et Liang, 1985 and C. macrofurcula Mao et Ou, 2000 are transferred to Longchuanacris as new combination, and the male of the former is newly described. The specific name C. macrofurcula Mao et Ou, 2000 is replaced with L. viridus Mao et Ou, nomen nov.. A revised generic diagnosis and a key to the male of known species are given. All five species, including type species L. macrofurculus Zheng et Fu, 1989, are distributed in southwestern Yunnan, China. All specimens are deposited in the College of Life Sciences and Chemistry, Dali University (CLDU), Yunnan Province, China.